Physical Extraction Of Flagellavia Ultrasonication From Bacillus Subtilis 168 With Various Control Elements - Yan Leong, Kah (Pusat Pengajian Teknologi Industri, 2020)
Flagella was commonly known as the tail of bacteria. The major structural protein of bacterial flagella is called flagellin. Flagella have a potential to become biodegradable nanotube and important for drug delivery, electronic or semiconductor. There are still lack of research about flagella separation and purification. In this research, the morphology of the flagella and basal body for Bacillus subtilis 168 was investigated by scanning electron microscope and transmission electron microscope. The characterization of flagella was found that difference between flagella and cell body is nitrogen (N), magnesium (Mg) and Sulphur (S) by energy-dispersive X-ray spectroscopy. Statistically designed experiment revealed significant effects of sonication duration and sonicator output power on the concentration of flagellin after sonication. The cell body of Bacillus subtilis 168 was started to breaked from 20 % sonicator output power.